Correlation of Serum Tissue Transglutaminase Antibody Levels and Marsh Grading of Duodenal Biopsy in Patients of Celiac Disease - Paul, Benjith; Kinra, Prateek; Nandi, Bhaskar; Prasad, AS (Annals of Pathology and Laboratory Medicine, 2019)
Background: Celiac disease (CD) is a chronic small intestinal immune-mediated enteropathy precipitated in genetically predisposed individuals by ingestion of wheat gluten and related proteins of barley and rye. It is an under-diagnosed gluten-sensitive enteropathy, usually presenting with atypical/extra-intestinal features. Duodenal biopsy is considered as the gold standard in the diagnosis of CD. Serum anti tissue transglutaminase (anti-tTG) antibodies is auto antibodies directed against tissue transglutaminase (tTG) enzyme. Aims and objective: The aim of the study is to find out the prevalence of CD among clinically suspected cases of malabsorption, to assess the correlation of anti-tTG levels with modified Marsh grading of duodenal biopsy, to find out sensitivity, specificity and predictive values of anti-tTG test and to calculate the cut off values of anti-tTG diagnostic of high grade CD. Methodology: The present study included 118 clinically suspected patients of malabsorption in which both duodenal biopsy and anti-tTG test was done. The mucosal damage graded according to the modified Marsh grading and anti-tTG tests were done in serum using ELISA kit. Results: The prevalence of CD among clinically suspected cases of malabsorption was 12.7%. The incidence was highest in middle aged male patients. The most common clinical symptom was chronic diarrhea and commonest presenting sign was anemia. Anti-tTG levels were found to be proportionately increasing with the severity of CD and showed a positive correlation(r=0.433). Patients with anemia and chronic diarrhea showed statistically significant (p value=0.0242 and 0.0089 respectively) mean anti-tTG levels in Celiac patients in relation to non-Celiac patients. Although the mean levels of anti-tTG was 6.3 times higher than baseline in grade 3 disease, the ROC analysis showed that anti-tTG in isolation had no significance in exactly grading the disease (AUC=0.30). Conclusion: Positive correlation was found between anti-tTG levels and modified Marsh grading. Anti-tTG showed proportionate increase with severity of duodenal damage. Anti-tTG test showed low sensitivity (42.86%) and high specificity (84.34%). Hence it is not a reliable tool in isolation to screen CD but should be used in combination with duodenal biopsy. It can be used to assess the severity of CD and for follow up.